EXPERT SYSTEM FORWARD CHAINING METHOD DIAGNOSA PADA PENYAKIT GINJAL - Fitriani, Eka; Siregar, Iqbal Kamil; Apridonal M, Yori (J-Com (Journal of Computer), 2024)
Abstract: The choice of problem regarding the type of kidney disease as the sample for this study is the fact that kidney disease is an important organ in our body's metabolic system, because of our busy activities, we often forget to take care of it. Irregular eating patterns, lack of fiber and mineral water intake, and consumption of high-calorie instant foods or drinks, without realizing it, make the kidneys work harder. Starting from the process of filtration, reabsorption, to augmentation of food substances below the kidneys through the blood. The aim of this research is to create an expert system for kidney disease using a web-based programming language that is capable of providing services to the public and conveying information related to kidney disease. Pre-research and research was carried out at the Abdul Manan Simatupang Kisaran Regional General Hospital starting from November to December 2023. In this research data collection was carried out using observation, interviews and literature study methods. The results of this research show that having an expert system for diagnosing kidney disease in humans can provide significant benefits, including the data processing and consultation process being carried out quickly and producing fairly accurate reports, thus making work more effective and efficient.      Keywords: Expert System; Kidney Disease; Forward Chaining Method.Abstrak: Pemilihan masalah menyangkut jenis penyakit Ginjal sebagai sampel penelitian ini, adalah kenyataan bahwa penyakitpenyakit Ginjal merupakan organ penting dalam sistem metabolisme tubuh kita, karena padatnya aktivitas, kita sering lupa untuk menjaganya. Pola makan yang tidak teratur, kurangnya asupan serat dan air mineral, serta konsumsi makanan atau minuman instan berkalori tinggi, tanpa sadar telah memperberat kerja ginjal. Mulai dari proses filtrasi, reabsorpasi, sampai augmentasi dari zat-zat makanan yang di bawah ke ginjal melalui darah. Adapun tujuan penelitian ini adalah Membuat suatu sistem pakar untuk penyakit Ginjal menggunakan bahasa pemrograman berbasis web yang mampu memberikan pelayanan kepada masyarakat dan penyampaian informasi yang berkaitan dengan penyakit Ginjal. Pra penelitian dan penelitian dilakukan di Rumah Sakit Umum Daerah Abdul Manan Simatupang Kisaran yang dimulai pada bulan Bulan November sampai dengan Desember 2023. Pada penelitian ini pengumpulan data dilakukan dengan menggunakan metode observasi, wawancara dan studi pustaka. Dari hasil penelitian ini menunjukkan bahwa dengan adanya sistem pakar diagnosa penyakit ginjal pada manusia, dapat memberikan manfaat yang cukup berarti antara lain proses pengolahan datanya dan proses konsultasi dilakukan dengan cepat serta menghasilkan laporan yang cukup akurat, sehingga membuat pekerjaan akan lebih efektif dan efisien.Kata kunci: Sistem Pakar; Penyakit Ginjal; Metode Forward Chaining